A probabilistic proof of an electric network property. Technical Note - Palacios, José Luis (Ciencia)
We give an elegant probabilistic proof of the fact that multiplying by the same constant the resistance of every resistor in an electric network implies that the effective resistance between any two nodes of the network is multiplied by the same constant.